2013
DOI: 10.1111/jopy.12012
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Regulation and Mechanisms of Action in Psychotherapy: A Theory‐Based Translational Perspective

Abstract: Psychotherapy is a complex, multi-layered process with the potential to bring about changes at multiple levels of functioning, from the neurobiology of the brain to the individual’s role in the social world. Although studies of the mechanisms by which psychotherapy leads to change continue to appear, there remains much to be learned about how psychological interventions work. To guide explorations of how and for whom particular treatment approaches lead to change, researchers can rely on theory to identify pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Functional neuroimaging results with adolescent substance users suggested that “change talk” inhibited activation in brain regions that respond to alcohol cues 75 or among cannabis users, increased activation in brain areas involved in introspection, which was in turn associated with reductions in cannabis use over 1-month follow-up 76 . The narrow focus on a single mechanism of change (e.g., change talk) suggests the potential utility of a micro-intervention approach to studying MOC, which can provide greater precision by targeting smaller units of cause and effect 77 , albeit with a trade-off in external validity.…”
Section: Reviewmentioning
confidence: 99%
“…Functional neuroimaging results with adolescent substance users suggested that “change talk” inhibited activation in brain regions that respond to alcohol cues 75 or among cannabis users, increased activation in brain areas involved in introspection, which was in turn associated with reductions in cannabis use over 1-month follow-up 76 . The narrow focus on a single mechanism of change (e.g., change talk) suggests the potential utility of a micro-intervention approach to studying MOC, which can provide greater precision by targeting smaller units of cause and effect 77 , albeit with a trade-off in external validity.…”
Section: Reviewmentioning
confidence: 99%
“…In the present study, we used an alternative design for investigating specific therapeutic components based on the implementation of a therapeutic microintervention that targets smaller units of cause and effect in a therapeutic setting (Strauman et al, 2012). A microintervention can be characterized as a discrete, time-limited application of a single, specified psychotherapeutic component or technique, which in this study was a 90-minute cognitive restructuring session.…”
Section: Microintervention Studiesmentioning
confidence: 99%
“…In the latter part of the session, cognitive restructuring skills were reinforced and practiced by applying them to two film clips. The film clips were 10-minute excerpts from the movies "Schindler's List" (Spielberg, 1993) and "Forrest Gump" (Zemeckis, 1994), both showing episodes identified in pilot testing as reliably inducing negative mood states. Both episodes also comprised positive aspects (e.g., friendship, solidarity, love, hope, willingness to help).…”
Section: Interventionsmentioning
confidence: 99%
“…Along with the study of overall treatment effects using randomized control trial designs, one promising avenue is to examine self-regulatory processes (Denissen et al, 2013) and other short-term processes underlying personality development (Wrzus & Roberts, 2016) in more details by means of microintervention designs (cf. Flückiger et al, 2012;Strauman et al, 2013). Such designs reflect controlled laboratory as well as naturalistic investigations of a specific therapeutic aspect to generate and test hypotheses about how change mechanisms can help changing personality traits.…”
Section: Understanding Shared Change Principlesmentioning
confidence: 99%